Perancangan Sistem Informasi Website COPIA (Corn Utopia) - Salman Al-Farisi; salsi kirana sya'bani; Ika Septia Anggraeni; Muhammad Alif Vidi; Annisa Aulia Rohim; Gema Prasasti Mindara (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Unequal and efficient distribution of crop yields is a challenge that is often faced in the corn farming industry. This can be detrimental to farmers because it results in a buildup of unsold corn crops in several areas. To overcome this challenge, a technology-based solution is needed so that it can reach customers easily by creating a website that aims to help equalize the distribution of corn harvests, with a more efficient system for managing corn supply and demand. By using an Agile approach in website development, It is hoped that it can produce a system that suits user needs in a short time. The design stage will be carried out using the Unified Modelling Language (UML) approach. In black box testing, it was proven that the use of websites to equalize agricultural products has been proven to be able to build a more efficient system for managing corn supply and demand. In addition, the services provided through the website can reduce product distribution costs and speed up the buying and selling process with customers.